Toll-9 interacts with Toll-1 to mediate a feedback loop during apoptosis-induced proliferation in Drosophila - Alicia Shields; Alla Amcheslavsky; Elizabeth Brown; Tom V. Lee; Yingchao Nie; Takahiro Tanji; Y. Tony Ip; Andreas Bergmann (Cell Reports, 2022)
Summary: Drosophila Toll-1 and all mammalian Toll-like receptors regulate innate immunity. However, the functions of the remaining eight Toll-related proteins in Drosophila are not fully understood. Here, we show that Drosophila Toll-9 is necessary and sufficient for a special form of compensatory proliferation after apoptotic cell loss (undead apoptosis-induced proliferation [AiP]). Mechanistically, for AiP, Toll-9 interacts with Toll-1 to activate the intracellular Toll-1 pathway for nuclear translocation of the NF-κB-like transcription factor Dorsal, which induces expression of the pro-apoptotic genes reaper and hid. This activity contributes to the feedback amplification loop that operates in undead cells. Given that Toll-9 also functions in loser cells during cell competition, we define a general role of Toll-9 in cellular stress situations leading to the expression of pro-apoptotic genes that trigger apoptosis and apoptosis-induced processes such as AiP. This work identifies conceptual similarities between cell competition and AiP.